Diversity of Muroid rodent communities in key habitats of the Skole Beskids (Eastern Carpathians) - Stetsula, N.; Barkasi, Z.; Zagorodniuk, I. (Праці теріологічної школи, 2016)
Quantitative and qualitative analysis of the structure of muroid rodent communities has been conducted in nine biotope types of the Skole Beskids National Park. Indices of species and taxonomic richness, as well as of species and taxonomic diversity are presented. The highest taxonomic richness of muroid rodents has been revealed in beech-spruce forests, clearcuttings, and meadows. These biotopes are most capable to maintain high species diversity. The high species diversity in meadows is related to the variety of meadow cenoses according to elevation, type of neighboring biotopes, and origin. The highest taxonomic diversity characterizes hornbeam-beech, beech, and mixed forests indicating high stability and sustainability of muroid rodent communities in them, because these are biotopes with native phytocenoses. The rodents’ species diversity within the park is maintained by the diversity of biotopes, their area and available trophic resources. Diversity indices have a functional relation with the taxonomic richness, which allows estimating diversity by the species richness and avoid calculations of diversity indices.